Assessment of eco-tourism activities, soil erosion in the riverbank, riparian vegetation and the community's socio-demographic and economic profile in the Lobor River, Bohol, Central Philippines basic data for impact mitigation - Asane, Desiderio C. (Cebu City University of the Philippines in the Visayas, Cebu College, 2005)
Loboc River, as an eco-tourism site, must be sustainable to support the growing demand of tourists and maximize multiple uses and services the river is offering to the community. An assessment of eco-tourism activities, soil erosion in the riverbank, status of riparian vegetation, and the community's socio-demographic and economic profile was undertaken to determine the existing condition with focus on the changes that have occured in the Lobc River system. The data generated from the study may be used as basis for mitigating impacts associated with eco-tourism. Different parameters such as level of motor boating activities, land surface area loss (LSAL), sedimentation rate (SR), vegetation profile, ad the community's socio-economic and demographic state including the level of knowledge, perception and attitude were measured. The protion of the river that was assessed was limited only to the area within the jurisdiction of the Loboc town, covering 15 barangays where the Loboc River traverses. Three sites were chosen for the study area with both sides of the river sampled. The first site was located in the lower midstream (site A), the second site at the upper downstream (site B), while the third site at the lower downstream (site C). Direct observations on motor boating activities were conducted only in sites B and C, where these activities were observed to be prevalent. LSAL and SR determination including vegetation quadral sampling were done in 3 stations of each site. Interview with respondents from the community was only from 13 out of the 15 barangays. Activities were conducted within one-month period both for dry and wet season. Results of the study showed that the Loboc River is now facing a serious problemm in terms of soil erosion along its bank. The high frequency of motor boating trips during summer time had exposed the riverbanks to continued stress contributing to higher rate of erosion than during the wet season. Data gathered from land surface area loss and sedimentation rate determination, respectively, showed differences in the degree of the quality of soil loss in the riverbank and the trapped sediments. This is mainly due to differences in the degree of erosion forces that include the effects of motorized boats. Moreover, river tributaries also had an effect on the amount of trapped sediments because of soil-run-off being carried down during rain period. Erosion rate in the lower mainstream was slower than that of the downstream area. On the other hand, the rate of erosion in the upper downstream was faster than that of the lower downstream portion. This condition can be attributed to the higher number of motr boating trips in the upper downstream that resulted to higher of waves that accelerated faster erosion process in the bank. Based on the findings of the study, recommendations were suggested for the rahabilitation of the eroded of the study, recommendations were suggested for the rehabilitation of the eroded riverbank, particularly in the downstream portion, as well as proper management and procedures of operating motorized boats in the river system for the continuance of eco-tourism and the sustainability of the Loboc River resource.
Thesis--(M.S. Environmental Studies) --Graduate Committee Natural Sciences and Mathematics Divisions, U.P. in the Visayas Cebu College, August 2005.
Keywords: Eco-tourism -- Loboc River, Bohol